1982
DOI: 10.1530/acta.0.0990636
|View full text |Cite
|
Sign up to set email alerts
|

Vast release of submaxillary mouse renin to saliva after stimulation with cholinergic, β-adrenergic but especially α-adrenergic agonists

Abstract: \g=a\-adrenergic stimulation with phenylephrine causes release of vast amounts of mouse submaxillary gland renin to saliva. The amount released is about 100-fold higher than that released after \g=b\-adrenergic stimulation with isoproterenol and about 1000-fold higher than the amount released after cholinergic stimulation with pilocarpine. \g=a\-blockadewith phenoxybenzamine before phenylephrine stimulation strongly inhibits the renin release. However, phenoxybenzamine or \ g = b \ \ x = r e q -\ blockade with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The vast renin concentration in aggression-provoked saliva, which may be mimicked by a-adrenergic stimulation, 5 reaches values of 6000 GU x ml" 1 (Pedersen EB, Poulsen K, unpublished data). Such high concentrations are a hazard to all physiological studies because of the risk of contamination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vast renin concentration in aggression-provoked saliva, which may be mimicked by a-adrenergic stimulation, 5 reaches values of 6000 GU x ml" 1 (Pedersen EB, Poulsen K, unpublished data). Such high concentrations are a hazard to all physiological studies because of the risk of contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Since a-adrenergic stimulation with phenylephrine provokes a vast renin release in the saliva, 5 it was …”
Section: Stimulation Of Renin Containing Saliva From Unidentified Salmentioning
confidence: 99%
“…These lymphoid tissues represent the site of B cell activation and the inducer for cytotoxic T-lymphocytes. 4 In addition to the immune function and the well-known exocrine function, many researchers have demonstrated that SGs have an endocrine function 5 , 6 such as secretion from rodent SMG into the blood has been demonstrated for glucagon, 7 EGF, 8 NGF, 9 renin 10 , kallikrein 11 , and sialorphin 12 , 13 . Additionally, parotid gland endocrine secretion has been confirmed for a protein complex originally extracted from bovine parotid glands 14 and amylase.…”
Section: Introductionmentioning
confidence: 99%